Review on effects of pre and post-harvest factors affecting the quality and shelf life of tomato (Lycopersicon esculentum Mill.) - Ashwini A (African Journal of Environmental Economics and Management, 2023)
Tomato is one of the most popular produced and extensively consumed vegetable crops in the world and belongs to Solanaceae family. Tomato production can serve as a source of income for most rural and per urban producers in most developing countries of the world. However, postharvest losses make its production unprofitable in these parts of the world. Postharvest losses in tomatoes can be as high as 25- 42% globally. Postharvest losses in tomatoes can be either quantitative or qualitative. The postharvest quality status of tomatoes partly depended on some pre harvest practices carried out during production some of these factors are climate, fertilizer application, pruning, maturity stage, cultivar selection, and irrigation and also using best postharvest handling practices or factors such as temperature, relative humidity, gases in storage, postharvest calcium chloride application, and physical handling procedures to maintain the quality after harvest was also critical. The potential for solving some of the problems related to tomato quality and its postharvest maintenance through excellent genetic manipulations by plant breeders and work improving the nutritional quality and technology of modified atmospheres application within consumer packages, pallets, and transport vehicles a high priority in future research. The main objective of this seminar paper is to review effect of pre harvest and postharvest factors affecting the quality and shelf life of harvested tomatoes.